TECHNOLOGIES AND ARCHITECTURES OF THE INTERNET-OF-THINGS (IOT) FOR HEALTH AND WELL-BEING - Shukla, Tushar Dhar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A healthcare system is a collection of hardware and software tools designed to offer individuals, such as patients and healthcare professionals, a variety of healthcare services and applications with the goal of enhancing health and well-being in a way that is both broadly applicable and practically applicable. The goal of a healthcare system is to improve health and well-being in a way that is both broadly applicable and practically applicable. The Internet of Things offers novel concepts, methods, and possible answers that can contribute to the development of new ways to enhance the delivery of healthcare in its current form. In addition, the Internet of Things may offer the chance to improve upon the medical processes that are now in use in order to give patients with customised medical treatment. By leveraging open-source platforms and operating systems, it is possible to increase the overall level of quality, safety, and accessibility of healthcare systems. This is one such method that may be utilised for the aforementioned enhancement. Because they make it possible for devices, programmes, and entire systems to reliably expose application programming interfaces (APIs) to one another, open-source solutions that are already in existence may also be able to improve the process of building and operating healthcare information systems. It's possible that this will be beneficial to the healthcare business. Because of this, interoperability will improve, and the costs associated with administering and maintaining networks consisting of numerous devices will decrease. At the present time, members of the general public have access to a wide range of open-source technology. These kinds of technology are often available online for general use. These technologies provide platforms that are safe and cost-effective, making them perfect for building and prototyping state-of-the-art healthcare solutions.